2017
DOI: 10.1016/j.tube.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The minipig as an animal model to study Mycobacterium tuberculosis infection and natural transmission

Abstract: In endemic countries more than 20% of tuberculosis (TB) cases are in infants and children. Current animal models study TB during adulthood but animal models for infant TB are scarce. Here we propose that minipigs can be used as an animal model to study adult, adolescent and infant TB including natural transmission. In these studies, two-month old minipigs (representing infant age in humans) and six-month old minipigs (representing adolescence in humans) were infected via the aerosol route with hyper-virulent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 27 publications
4
22
0
Order By: Relevance
“…Minipigs are a genetically selected species, which is more convenient than other pigs for experiments in a lab, mainly for size reasons. Experimental results in TB in minipigs resemble pathological findings described in human [21][22][23].…”
Section: Plos Computational Biologysupporting
confidence: 61%
“…Minipigs are a genetically selected species, which is more convenient than other pigs for experiments in a lab, mainly for size reasons. Experimental results in TB in minipigs resemble pathological findings described in human [21][22][23].…”
Section: Plos Computational Biologysupporting
confidence: 61%
“…M. tuberculosis can be transmitted not only between humans and animals but also between animals through similar transmission routes found in humans. Ramos et al [207] reported that when W-Beijing M. tuberculosis HN878 infected or unchallenged minipigs were housed together, active M. tuberculosis could be identified in the pulmonary and thoracic lymph nodes from both infected and unchallenged minipigs. Furthermore, it is gradually becoming recognized that vaccination of domestic animals may be an alternative long-term strategy for controlling the transmission of TB [208].…”
Section: New Technologies and Tools Open New Avenues For The Use Of Amentioning
confidence: 99%
“…Overall, these studies prove the potential pigs have for modeling TB. Upon Mtb infection, pigs develop similar pathological changes in the lung tissue and parenchyma to humans, including pulmonary tubercles with caseous necrosis, followed by liquefaction and cavity formation (Ramos et al, 2019;Helke et al, 2006), and mount immune responses that recapitulate the human response to Mtb infection and BCG vaccination (Gil et al, 2010;Lee et al, 2004;Ramos et al, 2019;Ramos et al, 2017). This, combined with their size and anatomy ( Table 2), affirms that neonatal pigs are suitable models for neonatal and infant human TB vaccine research.…”
Section: Pigsmentioning
confidence: 73%
“…Our group used an aerosol route to infect 2-month-old and 6month-old miniature pigs, representing the respective human infancy and adolescence, with the hypervirulent strain Mtb HN878 (Ramos et al, 2017). We observed pathological changes, such as caseous necrosis and calcified lesions in the lungs and lymph nodes, recovered viable bacteria from both tissues, and demonstrated natural aerosol transmission from infected to uninfected pigs housed together (Ramos et al, 2017). Further, our group studied the immune response of neonatal piglets that were vaccinated with BCG at birth and challenged with MtB at 20 weeks of life (Ramos et al, 2019).…”
Section: Pigsmentioning
confidence: 99%
See 1 more Smart Citation